Trends and contributors of complete continuum of maternal healthcare service utilization in Ethiopia: a multivariate decomposition analyses - Ayal Debie; Molla M. Wassie; Claire T. Roberts; Murthy N. Mittinty; Annabelle Wilson; Jacqueline H. Stephens (Reproductive Health, 2025)
Abstract Background Most maternal deaths are preventable by accessing essential maternity healthcare services. However, maternal mortality rates remain high in Ethiopia partly due to only a few women using a complete Continuum of Maternal Healthcare Services (CMHS). This study aims to assess trends and contributors for complete CMHS utilization in Ethiopia. Methods Ethiopian Demography and Health Survey (EDHS) 2011–2019 data were used to assess the trends of complete CMHS utilization. A total weighted sample of 10,768 women (3333 in 2011, 4590 in 2016, and 2845 in 2019) were included in the analysis. A logit-based multivariate decomposition analysis was undertaken to assess the change in the proportion of complete CMHS utilization and its contributors between 2011 and 2019. Results In Ethiopia, trends of complete CMHS utilization among women increased from 9.6% (95% CI 8.4, 10.9) in 2011 to 29.9% (95% CI 27.3, 32.6) in 2019. In the decomposition analysis, 60.6% of the difference in the proportion of complete CMHS utilization was explained by the differences in the composition of women’s characteristics, and 39.4% was attributed to coefficients of characteristics. As such, equalizing the number of women who attended school at secondary level or higher, had television, initiated antenatal care (ANC) visits in the first trimester, were aware of pregnancy-related complications, delivered by caesarean section for their most recent childbirth, were from poorer households, gave urine and blood samples during pregnancy in 2019–2011 levels, would reduce the differences between 2011 to 2019 in complete CMHS utilization. In contrast, equalizing the number of women from richer (higher) household wealth categories in 2019–2011 levels would increase the 2011–2019 gaps in complete CMHS utilization. Conclusion While progress has been made, complete CMHS utilization was low in Ethiopia. Differences in the composition of characteristics and effect of coefficients had a substantial contribution to the change in complete CMHS utilization between 2011 and 2019. Adopting a multi-faceted approach that considers the unique challenges within the country, including women's education, wealth status, and quality of care, will improve CMHS utilization. Empowering women through education can enhance their decision-making ability regarding their own health.